1995
DOI: 10.1007/bf01275216
|View full text |Cite
|
Sign up to set email alerts
|

Content of iron and copper in the nuclei and induction of pH 9-labile lesions in L5178Y sublines inversely cross-sensitive to H2O2 and x-rays

Abstract: Cells from the L5178Y murine lymphoma subline LY-R are twice as resistant to killing by ionizing radiation than the subline LY-S. In contrast, LY-R cells are more sensitive to killing by H2O2, the effect being more pronounced at 37 degrees C than 0 degree C. Initial DNA damage after H2O2 treatment (both temperatures, 5 min) has been estimated by the 'comet' assay (single-cell gel electrophoresis) and fluorescent halo technique. According to both methods, the initial damage is significantly higher in LY-R cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The LIP level in LY-R cells is 3-times higher than in LY-S cells (Lipinski et al, 2000) (Table 1). Interestingly, it is well correlated with the content of iron in L5178Y cell nuclei, previously measured by flame atomic absorption spectrometry (Szumiel et al, 1995) (Table 1).…”
Section: Lip Level In L5178y Cells Is Associated With Iron Content Insupporting
confidence: 67%
See 2 more Smart Citations
“…The LIP level in LY-R cells is 3-times higher than in LY-S cells (Lipinski et al, 2000) (Table 1). Interestingly, it is well correlated with the content of iron in L5178Y cell nuclei, previously measured by flame atomic absorption spectrometry (Szumiel et al, 1995) (Table 1).…”
Section: Lip Level In L5178y Cells Is Associated With Iron Content Insupporting
confidence: 67%
“…Interestingly, Petrat et al (2001) found that hepatocyte nucleus contained 6.6 ± 2.9 mM of Total Fe content in the nucleus (ng/10 6 cells) (Szumiel et al, 1995) 7.7 ± 1.8 3.1 ± 0.9 2.48 chelatable iron. Although the amount of total concentration iron in hepatocytes was estimated to be similar to that of the cytoplasm (Lai et al, 1996), a surprisingly high content of redox-active iron in the nucleus presents a hazard of DNA damage.…”
Section: Lip Level In L5178y Cells Is Associated With Iron Content Inmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the amount of initial DNA damage [1,3] and iron content [3] contribute to the difference in sensitivity to hydrogen peroxide. Further experimental data [4] pointed to a lower efficiency of the antioxidant defense system in the hydrogen peroxide-sensitive LY-R cells than in the hydrogen peroxide-resistant LY-S cells.…”
Section: Introductionmentioning
confidence: 97%
“…H202 is known to induce single strand DNA breaks in mammalian cells 17,18 In combination with L-histidine also double strand breaks are induced for 11202 concentrations above 20 jiM 19 The reason and the mechanism for this interaction is not completely understood 18 However, as for ionizing radiation, intracellular misrepair of the double strand breaks leads to a complex pattern of chromosome aberrations including dicentric chromosomes20. H202 is known to induce single strand DNA breaks in mammalian cells 17,18 In combination with L-histidine also double strand breaks are induced for 11202 concentrations above 20 jiM 19 The reason and the mechanism for this interaction is not completely understood 18 However, as for ionizing radiation, intracellular misrepair of the double strand breaks leads to a complex pattern of chromosome aberrations including dicentric chromosomes20.…”
Section: Introductionmentioning
confidence: 99%